Improvement in thermal durability of fluorinated rubber by the addition of single-walled carbon nanotubes as a thermally stable radical scavenger. (16th June 2017) - Ata, Seisuke; Tomonoh, Shigeki; Yamda, Takeo; Hata, Kenji
Abstract: Rubber is an excellent material, but its usage has been limited due to its low heat-resistance. In a high-temperature environment, rubber decomposes due to the heat radicals generated by the bond cleavage reaction. In order to improve the heat-resistivity of rubber, it is necessary to stabilize the radicals. Therefore, carbon nanotubes (CNTs), which are known for their excellent radical scavenging ability, were added to fluorinated rubber. The upper limit of the temperature for continuous use was increased from approximately 200 to 340 °C with the addition of the small amount of CNTs. This technology would make it possible to easily improve the heat resistivity of rubber and would expand their use in a variety of applications that were previously limited due to the issues of heat-resistivity. Graphical abstract: Highlights: Thermal resistivity of fluorinated rubber (FKM) improved by carbon nanotubes. Carbon nanotubes act as a radical scavenging material to protect auto-oxidation. Smaller diameter of CNTs shows higher effect for improving thermal resistivity of FKM.